KUALITAS KIMIA DAN KANDUNGAN KLOROFIL TANAMAN ALFALFA (Medicago sativa L.) DENGAN LAMA PENYINARAN DAN DOSIS DOLOMIT YANG BERBEDA PADA TANAH REGOSOL - Hermanto Hermanto; Bambang Suwignyo; Nafiatul Umami (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study aimed to analyze the quality of chemical and chlorophyll content of alfalfa plants with lenght of irradiation and dose of dolomite on the regosol soil. The experiment was conducted implemented in Greenhouse Laboratory Forage and Pasture Faculty of Animal Sciences University of Gadjah Mada, from May to September 2015. This study used a Completely Randomized Design (CRD) 3 x 3 factorial design with two factors treatments and four replications. The first factor is the dose of dolomite (D) with 3 treatment (D0 = without dolomite, D1 = dolomite 6 t/hectare or 90 g/polybag and D2= dolomite 12 t/hectare or 180 g/polybag). The second factor is the length of irradiation (C) with 3 treatments (C0 = irradiating 12 hours, C1 = irradiating 14 hours and C2 = irradiating 16 hours). Data were statistically analyzed using analysis of variance and significant results continued with Duncan test at 5% level.Parameters measured were the proximate analysis (dry matter, organic matter, crude protein, crude fiber, crude fat, ash) and alfalfa chlorophyll content. The results showed that there was no significant interaction effect between lenght of irradiation and dose of dolomite treatment to the dry matter content, organic matter, crude protein, crude fiber, crude fat, ash and alfalfa chlorophyll content. The treatment lenght of irradiation are significant (P<0,05) of the organic matter content and ash content of alfalfa. Dose of dolomite treatment was not significant on all parameters of the study. The results showed that the treatment and dosage of radiation are dolomite not significant on the production of plant fresh weight, dry weight of plants, dry matter content, organic matter, crude protein, crude fiber, crude fat, ash and content alfalfa chlorophyll. No interaction between treatment and dosage of radiation are dolomite which significantly affect production plant fresh weight, dry weight of plants, dry matter content, organic matter, crude protein, crude fiber, crude fat, ash and alfalfa chlorophyll content. (Keywords: Alfalfa, lenght of irradiation, dolomite, regosol soil)